Lung adenocarcinoma with Lambert–Eaton myasthenic syndrome indicated by voltage-gated calcium channel: a case report - Arai, Hiromasa (BioMed Central, 2012)
INTRODUCTION: Lambert–Eaton myasthenic syndrome is a rare disorder and it is known as a paraneoplastic neurological syndrome. Small cell lung cancer often accompanies this syndrome. Lambert–Eaton myasthenic syndrome associated with lung adenocarcinoma is extremely rare; there are only a few reported cases worldwide. CASE PRESENTATION: A 75-year-old Japanese man with a past history of chronic rheumatoid arthritis and Sjögren syndrome was diagnosed with Lambert–Eaton myasthenic syndrome by electromyography and serum anti-P/Q-type voltage-gated calcium channel antibody level preceding the diagnosis of lung cancer. A chest computed tomography to screen for malignant lesions revealed an abnormal shadow in the lung. Although a histopathological examination by bronchoscopic study could not reveal the malignancy, lung cancer was mostly suspected after the results of a chest computed tomography and [(18)F]-fluorodeoxyglucose positron emission tomography. An intraoperative diagnosis based on the frozen section obtained by tumor biopsy was adenocarcinoma so the patient underwent a lobectomy of the right lower lobe and lymph node dissection with video-assisted thoracoscopic surgery. The permanent pathological examination was the same as the frozen diagnosis (pT2aN1M0: Stage IIa: TNM staging 7th edition). Immunohistochemistry revealed that most of the cancer cells were positive for P/Q-type voltage-gated calcium channel. CONCLUSIONS: Our case is a rare combination of Lambert–Eaton myasthenic syndrome associated with lung adenocarcinoma, rheumatoid arthritis and Sjögren syndrome, and to the best of our knowledge it is the first report that indicates the presence of voltage-gated calcium channel in lung adenocarcinoma by immunostaining.